Perceptions of Students and Staff of the National Open University of Nigeria on the Quality of Online Instructional Delivery Strategy: An Evaluative Study - Aminin, Clifford Moses; Salawu, Ibrahim O. (West African Journal of Open and Flexible Learning, 2014)
Some faculty members of the School of Education, National Open University of Nigeria, implemented a hybrid online and face-to-face instruction in teaching course for the Post Graduate Diploma in Distance Education (PGDDE) programme in the 2012/2013 academic year. This study explores the rationale for the use of this particular mode of delivery; faculty conclusions regarding implementation of this mode, and the impact of this mode on learning. Comparisons of students of the programme using some or all the quality indices of the online mode with the face-to-face strategies were also investigated and analysed. The study established that faculty staff and students viewed the online instructional mode as favourable. The mean students’ ratings (mean=3.22, and 3.38 for quality and amount of content learnt) for the dimensions of instructional quality were the same for online and face-to-face course delivery formats. Students also rated online interactive instruction higher than the face-to-face on the ease of access to the course material dimension of effectiveness; (mean=3.43 and 3.42 respectively). These findings suggest that it is possible to achieve levels of effectiveness in an online instructional format similar to those that are found in face-to-face delivery. Students of the PGDDE programme also rated student's collaborations highly, (mean=3.58 and 3.31), suggesting that faculty may capitalise on available mechanisms for interaction and collaboration.
Keywords: Asynchronous online courses; instructional delivery effectiveness; faculty interaction; quality of instruction